Spinal parenchymal occupation by neural stem cells after subpial delivery in adult immunodeficient rats - Marsala, Martin; Kamizato, Kota; Tadokoro, Takahiro; Navarro, Michael; Juhas, Stefan; Juhasova, Jana; Marsala, Silvia; Studenovska, Hana; Proks, Vladimir; Hazel, Tom; Johe, Karl; Kakinohana, Manabu; et al. (Stem cells translational medicine, 2020)
Neural precursor cells (NSCs) hold great potential to treat a variety of neurodegenerative diseases and injuries to the spinal cord. However, current delivery techniques require an invasive approach in which an injection needle is advanced into the spinal parenchyma to deliver cells of interest. As such, this approach is associated with an inherent risk of spinal injury, as well as a limited delivery of cells into multiple spinal segments. Here, we characterize the use of a novel cell delivery technique that employs single bolus cell injections into the spinal subpial space. In immunodeficient rats, two subpial injections of human NSCs were performed in the cervical and lumbar spinal cord, respectively. The survival, distribution, and phenotype of transplanted cells were assessed 6-8 months after injection. Immunofluorescence staining and mRNA sequencing analysis demonstrated a near-complete occupation of the spinal cord by injected cells, in which transplanted human NSCs (hNSCs) preferentially acquired glial phenotypes, expressing oligodendrocyte (Olig2, APC) or astrocyte (GFAP) markers. In the outermost layer of the spinal cord, injected hNSCs differentiated into glia limitans-forming astrocytes and expressed human-specific superoxide dismutase and laminin. All animals showed normal neurological function for the duration of the analysis. These data show that the subpial cell delivery technique is highly effective in populating the entire spinal cord with injected NSCs, and has a potential for clinical use in cell replacement therapies for the treatment of ALS, multiple sclerosis, or spinal cord injury.
Keywords: Parenchymal Tissue; Rats, Sprague-Dawley; neuraxial neural precursor migration; Rats; human-specific mRNA sequencing; glia limitans formation from grafted neural precursors; zvířata; immunodeficient rat; parenchymatická tkáň; Neural Stem Cells; subpial stem cell injection; potkani Sprague-Dawley; krysa rodu Rattus; nervové kmenové buňky; Animals